Medical Image Segmentation Based on a Hybrid Region-Based Active Contour Model. (16th June 2014) - Liu, Tingting; Xu, Haiyong; Jin, Wei; Liu, Zhen; Zhao, Yiming; Tian, Wenzhe
Abstract : A novel hybrid region-based active contour model is presented to segment medical images with intensity inhomogeneity. The energy functional for the proposed model consists of three weighted terms: global term, local term, and regularization term. The total energy is incorporated into a level set formulation with a level set regularization term, from which a curve evolution equation is derived for energy minimization. Experiments on some synthetic and real images demonstrate that our model is more efficient compared with the localizing region-based active contours (LRBAC) method, proposed by Lankton, and more robust compared with the Chan-Vese (C-V) active contour model.